2021
DOI: 10.5005/jp-journals-10071-23723
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestations of COVID-19: A Series of Seven Cases

Abstract: H ighlights There is no dearth of literature on pulmonary involvement in COVID-19 infection. However, extra-pulmonary manifestations are rare and can be easily missed during this pandemic. Our case series hopes to highlight the fact that neurological manifestations of COVID-19 infection are likely to be overlooked. Hence, a low threshold of clinical suspicion and testing for COVID-19 infection is needed in cases presenting with primary neurological symptoms. This will facilitate quicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Filosto et al [14] published a series of 34 GBS cases in the North Italian population of 8.4 million, and calculated a rate of 47.9 cases of GBS per 100 000 COVID-19 infections. In a prior case series published by our hospital (Goel et al [15]), we have also reported neurological manifestations of COVID-19 disease presenting to our hospital, out of which 2 presented with GBS.…”
Section: Discussionsupporting
confidence: 51%
“…Filosto et al [14] published a series of 34 GBS cases in the North Italian population of 8.4 million, and calculated a rate of 47.9 cases of GBS per 100 000 COVID-19 infections. In a prior case series published by our hospital (Goel et al [15]), we have also reported neurological manifestations of COVID-19 disease presenting to our hospital, out of which 2 presented with GBS.…”
Section: Discussionsupporting
confidence: 51%
“…On the opposite side, Goel et al [ 11 ] proved that the most commonly reported COVID neurological complications are cerebrovascular accidents, encephalopathy, encephalitis, meningitis, and Guillain-Barr e syndrome (GBS).…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of COVID-19 neurological manifestations requires the exclusion of alternate etiologies, including sepsis, metabolic, autoimmune, or critical illness neuropathy. Sepsis alone can result in encephalopathy or polyneuropathy in 70% of patients [2]. Critical illness neuropathy is a sensorimotor polyneuropathy that is often a complication of sepsis and multiorgan failure, occurring in 70% of such patients [3].…”
Section: Discussionmentioning
confidence: 99%
“…The novel coronavirus SARS-CoV-2 is commonly known to affect the respiratory system, but other organ systems, including the nervous system, can become dysfunctional as a result of severe illness. Central nervous system (CNS) manifestations like stroke, seizures, venous sinus thrombosis, meningitis, encephalitis, myelitis, and CNS vasculitis, and peripheral nervous system (PNS) manifestations like Guillain-Barre syndrome (GBS) and myopathy have been reported with COVID-19 infection [1,2]. Even with these known complications associated with severe COVID-19 infection, it is often difficult to distinguish whether the neurological features are manifestations of critical illness or specific to the virus itself.…”
Section: Introductionmentioning
confidence: 99%